COMMUNITY PRO-CONTRA PROJECT FOR THE PRESENCE OF THE OMNIBUS LAW BILL IN LEGAL SOCIOLOGY PERSPECTIVE - Deni Umbara; Jum Hermanto; Franky Ariyadi (Legal Standing : Jurnal Ilmu Hukum, 2020)
The Omnibus Law was first echoed during the inauguration of the President of theRepublic of Indonesia to be precise, on October 20, 2019. Omnibus Law is a legalconcept that will simplify a regulation. All the considerations are causedby too manyrules that have stagnated the economic growth experienced by this nation. With themany regulations, the president felt the need to take steps forward to minimize theseregulations. Acode was created that could back up all rules, namely the presence of theOmnibus Law Bill, which later the bill became a law called the Omnibus Law.Peoplewho reject and feel uneasy about the presence of the Omnibus Law Bill think that thisbill will only prioritize outside investment, making it a red carpet for foreign investors,the investment will only be enjoyed by the elite and a handful of people, which does notlead to job creation which will have an impact on improving people's welfare, makingworkers like production machines, loss of minimum wages, reducing overtime workinghours, and many other articles that castrate their own people. With the presence of thisbill, it will make this nation even more backward from democracy. The government andthe DPR should have drafted this law to protect and voice the voices of the peopleaffected by the regulations, not the other way around. Therefore, the people who are against it assess that the presence of this bill will legitimize investments that destroy the environment, ignore the assets of the people and indigenous peoples. The drafting ofthis bill was carried out behind closed doors without the participation of civil societyand recycled unconstitutional articles of centralization of authority that hurt the spiritof reform.